2002
DOI: 10.1002/chin.200214117
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Structure of 5‐Alkyl(aryl)pyrrol‐2‐ones.

Abstract: Synthesis and Structure of 5-Alkyl(aryl)pyrrol-2-ones. -Amination of 4-oxoalkanoic acids or their esters leads to the title pyrrolones (II), which exist in solution as a mixture of cyclic and open-chain isomers in ratios depending on the nature of the substituent at 5-position of the heterocycle. -(EGOROVA, A. YU.; SEDAVKINA, V. A.; TIMOFEEVA, Z. YU.; Chem. Heterocycl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In addition to providing a series of analogues, a synthesis of pure compounds would minimize the risk of false positives in further assays. A survey of the literature revealed that there have been previous reports of the synthesis of the core 3-alkylidene-4-pyrrolin-2-one scaffold 10. Many of these routes utilize 3-alkylidene-furan-2-ones as starting materials 10a,10d,11.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing a series of analogues, a synthesis of pure compounds would minimize the risk of false positives in further assays. A survey of the literature revealed that there have been previous reports of the synthesis of the core 3-alkylidene-4-pyrrolin-2-one scaffold 10. Many of these routes utilize 3-alkylidene-furan-2-ones as starting materials 10a,10d,11.…”
Section: Introductionmentioning
confidence: 99%